Chemical reaction modeling of industrial scale nitrocellulose production for military applications. Issue 7 (16th April 2020) - Sullivan, Francis; Simon, Laurent; Ioannidis, Nikolaos; Patel, Subhash; Ophir, Zohar; Gogos, Costas; Jaffe, Michael; Tirmizi, Shakeel; Bonnett, Peter; Abbate, Philip
Abstract: A model was developed to describe the nitration of cellulose in mixed acids used in the production of military grade nitrocellulose. Acid dissociation, swelling, diffusion, and chemical reaction were considered to model the nitration of industrially important cellulose materials for given reaction times and conditions. This model is supported by experimental work conducted to measure the dynamics of swelling and diffusion in wood pulp slivers, and the model was validated using the results of lab‐scale nitration reactions. Microcomputed tomography was also used to perform a structural analysis of wood pulp slivers that were cut on industrial, rotary cutting machines to evaluate features that may influence the reactivity of these materials.